Human Milk Oligosaccharide Composition of Breast Milk from Lactating Women in Dhaka, Bangladesh (P11-040-19). (13th June 2019) - Loutet, Miranda; Pell, Lisa G; Yonemitsu, Chloe; Ohuma, Eric O; Sturrock, Shelby; Azad, Meghan B; Mahmud, Abdullah Al; Ahmed, Tahmeed; Bode, Lars; Roth, Daniel
Abstract: Objectives: We aimed to describe the human milk oligosaccharide (HMO) composition of breast milk from Bangladeshi women, overall and by galactoside 2-alpha-L-fucosyltransferase 2 (FUT 2) secretor status, and to estimate the effect of prenatal and postpartum vitamin D3 supplementation on HMO composition. Methods: In a sub-study of the Maternal Vitamin D for Infant Growth trial in Dhaka, Bangladesh, we selected 96 participants from the placebo group and 96 who were administered 28, 000 IU/week vitamin D3 from 17–24 weeks gestation to 6-months postpartum. Breast milk collected at 13 ± 1 week(s) postpartum were analyzed by high-performance liquid chromatography to determine absolute concentrations, relative abundancies of 19 HMOs and total amount HMOs, summarized using medians (interquartile range (IQR)). Associations between each HMO and selected maternal factors (e.g., age, parity, breastfeeding pattern) were estimated by multiple linear regression, adjusting for vitamin D group. Results: Total median HMO concentration was 16.8 mmol/mL (IQR 9.5-18.7) overall, but varied by secretor status: 18.0 mmol/mL (IQR 16.9-19.2) in secretors (66%) and 9.2 mmol/mL (IQR 8.9-9.5) in non-secretors (34%). Individual HMO concentrations also varied within secretor groups: 2'FL, the most abundant HMO among secretors, ranged from 1.3 to 15.8 mmol/mL among secretors and LNFP II, most abundant among non-secretors, ranged from 0.02 to 4.3 mmol/mL among non-secretors. Vitamin D3 supplementation did not affect total or individual HMO concentration. Other maternal factors were not significantly associated with secretor status, total or individual HMO concentration; however, breastmilk collected during winter had a significantly higher concentration of 3'FL compared to breastmilk collected during spring. The proportion of secretors in Bangladesh was similar to cohorts in Africa and North America. Relative HMO concentrations within secretor groups were similar to other international cohorts. Conclusions: The HMO composition of breast milk from Bangladeshi women is predominantly determined by secretor status, similar to other countries worldwide. Further research is required to understand the effect of variations in HMO composition on infant health outcomes. Funding Sources: The Bill and Melinda Gates Foundation.